Assessment of various groundwater recharge methods in the lower Kelantan River Basin, Malaysia / Nur Hayati Hussin - Nur Hayati , Hussin (2020)
Groundwater recharge is a natural process to replenish the aquifer system. Since 1930s the groundwater demand has risen as it has supported 70% of water supply in Lower Kelantan River Basin. However, a comprehensive study on groundwater recharge mechanism has never been reported. This study evaluated various methods to identify recharge flow processes using stable isotopes of deuterium (2H) and oxygen-18 (18O), tritium (3H), radon (222Rn) and hydrogeochemical (HC) and quantify recharge rate using chloride mass balance (CMB), water table fluctuation (WTF), temperature-depth profile (TDP) and groundwater modelling coupled with water balance GM(WB) followed by the construction of a conceptual model of recharge mechanism. Stable isotope indicates local rainfall origin from monsoon meteoric air masses that have experienced primary and secondary evaporation while tritium indicates rainfall of modern water age of <5 year to 10 years. Rainfall is the main source of surface water and diffuse recharge into the groundwater system. The fast transmit time of rainfall runoff, that percolates and infiltrates through unsaturated zone into aquifer has recharged Layer 1 with modern water age while deep aquifer (Layer 2 and Layer 3) contains a mix of recharge water of modern to sub-modern water caused by long transmit time and mixing with available water in the aquifer. Isotopes and hydrogeochemical methods reveal that the interactions of river-groundwater and aquifer-aquifer within the basin were triggered by infiltration, leaking and mixing besides controlled by the major processes of silicate weathering, dissolution and ion exchange. Through this process, groundwater in shallow aquifer (Layer 1) evolved from CaHCO3 to NaHCO3 towards the coastal area. As the depth increases, groundwater shows a trend of depletion in stable isotopes, decreasing in tritium and increasing in radon concentration. Recharge estimation using CMB, WTF, TDP and GM(WB) showed high variability within 8% to 68% of annual rainfall. CMB ranges from 16% to 68%, WTF 11% to 19%, TDP 8% to 11%, and GM(WB) 11% of annual rainfall, respectively. At 11%, recharge from GM(WB) was the best method for estimation because the model was constructed and calibrated using locally derived input parameters. GM(WB) is the only method involved with calibration and validation process to reduce the uncertainty. The WTF method based on long-term hydrological records gives a reasonable recharge value, in good agreement with GM(WB) and these methods can be paired to ensure the reliability of recharge value approximation in the same ranges. Applying various methods has given insight into methods selection to quantify recharge at LKRB and it is recommended that a lysimeter is installed as a direct method to estimate recharge. The integrated outcomes of groundwater recharge mechanism is useful as a baseline study for effective and sustainable groundwater resources management at LKRB and Malaysia.